2021
DOI: 10.1038/s41598-021-97793-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isoflavone genistein on psoriasis in in vivo and in vitro investigations

Abstract: Genistein is applied worldwide as an alternative medicament for psoriasis (Ps) because of its anti-inflammatory activity and perceived beneficial impact on the skin. Hereby, we report our in vivo and in vitro investigations to supplement scientific research in this area. The reduction of clinical and biochemical scores in mild to moderate Ps patients taking genistein, its safety, good tolerability with no serious adverse events or discontinuations of treatment, no dose-limiting toxicities, negligible changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…At dosages of 16 mg/kg body weight, very few investigations have found any potential mild toxicity (clinically exhibited, such as nausea, pedal oedema, or breast soreness) [151] . When applied topically to the skin, genistein has been demonstrated to be modestly absorbed (with pH 6 buffer absorbing it the most) and to have essentially no negative effects, such as erythema or disturbance of the stratum corneum [152,153] . A study on the pharmaceutical formulation of genistein indicated that genistein HME (hot melt extrusion) was safe at doses of up to 3000 mg.…”
Section: Dosing and Toxicitymentioning
confidence: 99%
“…At dosages of 16 mg/kg body weight, very few investigations have found any potential mild toxicity (clinically exhibited, such as nausea, pedal oedema, or breast soreness) [151] . When applied topically to the skin, genistein has been demonstrated to be modestly absorbed (with pH 6 buffer absorbing it the most) and to have essentially no negative effects, such as erythema or disturbance of the stratum corneum [152,153] . A study on the pharmaceutical formulation of genistein indicated that genistein HME (hot melt extrusion) was safe at doses of up to 3000 mg.…”
Section: Dosing and Toxicitymentioning
confidence: 99%
“…In vitro models observed the impact of genistein (a soy-derived isoflavone known for its anti-inflammatory properties) on psoriatic cells [86]. Different studies on the dietary effects of PsA focused on omega-3 and omega-6 fatty acids, reporting that certain genetic profiles might reduce the risk of PsA in the presence of a high dietary intake of omega-3 [87].…”
Section: Genetic and Pathogenetic Aspects Of Psoriatic Arthritismentioning
confidence: 99%
“…Studies have also found that the addition of dietary products that are rich in antioxidants, such as beta-carotene and flavonoids, have been shown to improve psoriasis severity. 46,47 Additional clinical studies on specific dietary interventions and other diets are warranted.…”
Section: No Additional Findingsmentioning
confidence: 99%